Investigation of physical and thermo-chemical characteristics of biomass fuels from local agricultural residues - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Nithe, N. A.; Rony, J. I. (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Proper understanding on the thermo chemical properties of biomass is necessary for the design of thermo-chemical conversion systems. The present study was conducted for the selected species of Bangladeshi biomasses. In this study seven differenttypes of biomass from Bangladeshi agriculture residues such as rice husk, rice straw, jute stick, sugarcane bagasse, water hyacinth, dhaincha (Sesbania aculeata) and wheat straw were considered for detailed analysis. The analysis includes moisture content, bulk density, proximate analysis, elemental analysis, calorific values and thermo-gravimetric (TGA/DTG) properties. This study reports that the moisture content in all samples investigated is suitable to serve as feedstock for thermal conversion technologies. Compared to coal, agricultural residues biomass has a lower energy density and also lower ash content. Results from proximate analysis and TG-DTG curve also indicates that higher amount of ash content in rice straw and rice husk among the studied samples and highest decomposition rate is obtained from rice husk but lowest from water hyacinth. Highest activation energy was obtained from rice straw and lowest from sugarcane bagasse. Contents of nitrogen and sulfur are very low underlying potential environmental benefits of using agricultural residues as fuel. On the other hand, the content in ash-forming elements, especially in potassium is quite high in rice straw, water hyacinth and dhaincha. Preliminary results of this study could serve to establish a database of Bangladeshi biomass fuels or feedstock that would support decision making in terms of energy conversion technology selection and operating conditions setting.